2021
DOI: 10.3390/plants10102116
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Chemophenetic Analysis of Essential Oil from Leaves of Piper gaudichaudianum Kunth (Piperaceae) Using a New Reduction-Oxidation Index to Explore Seasonal and Circadian Rhythms

Abstract: The aromatic species Piper gaudichaudianum Kunth (Piperaceae) is widely used in Brazil for medicinal and ritualistic applications. In the current study, chemophenetic patterns were realized across season and circadian rhythm based on the chemical profile of essential oils (EOs) from leaves. Hydrodistilled essential oils were analyzed by GC-MS and GC-FID, and a new calculation of metabolite oxidation level, averaged for each individual molecule component of the EO, was used to explore the patterns of metabolism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(31 citation statements)
references
References 120 publications
(175 reference statements)
1
29
0
1
Order By: Relevance
“…A study managed by our group [21] showed nine chemotypes for P. gaudichaudianum (i.e., δ-cadinene, 1-epi-cubenol, longipinanol, viridiflorol, α-humulene, E-caryophyllene, germacrene B, dillapiole and bicyclogermacrene), confirming this pronounced phenotypic chemical plasticity. Furthermore, we showed that EOs from P. gaudichaudianum from Rio de Janeiro are normally the bicyclogermacrene chemotype.…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…A study managed by our group [21] showed nine chemotypes for P. gaudichaudianum (i.e., δ-cadinene, 1-epi-cubenol, longipinanol, viridiflorol, α-humulene, E-caryophyllene, germacrene B, dillapiole and bicyclogermacrene), confirming this pronounced phenotypic chemical plasticity. Furthermore, we showed that EOs from P. gaudichaudianum from Rio de Janeiro are normally the bicyclogermacrene chemotype.…”
Section: Discussionmentioning
confidence: 59%
“…The chemical data in Table 1 is evaluated using two 'indices', which is the Shannon index, and the recently developed oxy-reduction index (Ramos and Moreira Index: GM RO ) [21]. These evaluations demonstrated a trend in the context of clonal chemical heritability.…”
Section: Chemodiversity and Micromolecular Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…When volatiles are studied, they can either be in the form of an essential oil or as a solvent extract. Furthermore, chemophenetic studies can be enriched by acknowledging biosynthetic relatedness between components, or by using oxidation indices to add another layer of complexity to the analysis and tease out more relationships, particularly in the context of circadian rhythms [69].…”
Section: Chemophenetics Of Natural Volatiles and Essential Oilsmentioning
confidence: 99%